Barriers to HIV care in Uganda and implications for universal test-and-treat: a qualitative study. Issue 5 (4th May 2022) - Lofgren, Sarah M.; Tsui, Sharon; Atuyambe, Lynn; Ankunda, Leander; Komuhendo, Robina; Wamala, Nathan; Sadiq, Alisat; Kirumira, Paul; Srishyla, Diksha; Flynn, Andrew; Pastick, Katelyn A.; Meya, David B.; et al.
ABSTRACT: Achieving universal HIV test-and-treat will require targeted interventions for those with worse outcomes, including advanced HIV. We conducted qualitative, semi-structured interviews with healthcare workers (HCWs) and people living with HIV (PLWH) at 5 HIV clinics in Kampala, Uganda, to understand barriers to care. PLWH enrolled started/restarted on HIV treatment ≤3 months prior. PLWH were grouped as 1) "ART-experienced" or those restarted therapy after ≥12 months off, 2) ART naïve CD4 count <100 cells/uL "late presenters" or 3) ART naïve CD4 count >350 cells/uL "early presenters". In-depth interviews were conducted in Luganda, translated, and transcribed verbatim. Between May and August 2017, 58 PLWH and 20 HCWs were interviewed. High stigma and low social support emerged as themes among all as barriers to care. Alcohol abuse was a barrier for men. Fear of domestic violence and abandonment were barriers for women, limiting disclosure of their HIV status to their male partners. Clinic factors such as rapport with staff, distance, efficiency, and privacy impacted care. Future interventions to decrease delayed ART initiation should target stigma and social support. Assisted disclosure, contact tracing, and alcohol abuse treatment should be implemented. Strengthening client support, reducing wait times, and increasing privacy assurances would improve care-seeking behaviors.